Sperm preparation and egg activation for bovine Intra-Cytoplasmic Sperm Injection (ICSI) - Gómez-Martínez, J. (2019)
The major economic interest of the dairy cattle industry is the production of replacement females of high genetic merit for traits of commercial importance. Sex-sorted semen represents a key means of achieving this goal. Its combination with ICSI may be an efficient alternative to overcome the detrimental effects of cell sorting which renders sexed sperm less suitable for artificial insemination and/or in vitro fertilisation. However, bovine ICSI success is less than that observed in humans where ICSI is employed as the first choice for the treatment of male infertility. Failure in sperm chromatin decondensation and pronuclei formation are thought to be the principal problems linked to low fertilisation success and poor embryo development following bovine ICSI. However, another factor may be the ability of bull sperm to induce egg activation following ICSI. Therefore, the main aim of this study was to develop improved sperm preparations and suitable artificial oocyte activation (AOA) protocols. Sperm preparation focused on removal of acrosomal membranes by either heparin (Hep) in combination with Lysophosphatidylcholine (LPC) or high dose Calcium Ionophore A23187 (CaIo). Sperm decondensation was induced by Hep and L-glutathione (GSH). Conditions were optimised to attain the maximum percentage viable fully-Acrosome Reacted (AR) spermatozoa and decondensed sperm heads. Similarly, new combinations of AOA protocols following ICSI were also investigated. These used strontium chloride (SrCl2) as the principal activating agent to enhance embryo development. Finally, 2 pronuclei formation (PN, 16 h post-activation), cleavage (Day 2) and blastocyst development (Day 8) were evaluated following ICSI using bull spermatozoa pre-treated differently and egg activation by the newly developed protocol (CaIo+SrCl2/CHX) which led to higher parthenogenetic embryo development (36%) compared to conventional protocols (~22%). These studies revealed that male gamete pre-treatment increased pronuclear formation (Hep+LPC- or CaIo-2PN = 32% vs. non-treated-2PN = 5%) following ICSI. Despite this improvement in bovine ICSI success, however, blastocyst development requires further enhancement because the percentage inseminated eggs that reached the blastocyst stage (~6%) and quality were poor compared to conventional IVF (23% blastocysts of inseminated). Therefore, further research is required to develop more suitable sperm preparation protocols to fertilise and activate eggs following ICSI in the absence of AOA. Similarly, other factors such as oocyte source (abattoir vs OPU) and maturation system that lead to greater post-insemination competency should be investigated.